"M. Zola n'observe plus": The Bourgeois Type in Zola's Pot-Bouille. Issue 3 (2nd July 2020) - O'Neil-Henry, Anne
Abstract: In this article, I analyze Zola's often-understudied 1882 novel of the bourgeois apartment building, Pot-Bouille, to show how it stages the particular impossibility of accurately capturing the nineteenth-century bourgeois type and, more generally, a critique of naturalist method. Pot-Bouille exposes the hypocritical, even deceptive nature of the immeuble 's residents through scenes where the narrator is the only one able to observe their duplicitous behavior; simultaneously, it offers numerous instances of imperceptibility or events that cannot be documented or observed. Studying this work alongside Zola's own preparatory notes and the novel's critical reception, I suggest that in this urban novel of the interior, the theories of observation imagined by the naturalist author (and by the first sociological thinkers too) prove at once indispensable and impossible. Ultimately, I argue that in its attempt to expose the difficulties in reducing the bourgeois to a knowable or essential type, Pot-Bouille anticipates twenty-first century scholars such as Sarah Maza, Franco Moretti, and others who write about the porous, even mythical nature of the concept of the bourgeoisie .